Functional Outcome of Primary Total Hip Arthroplasty using Harris Hip Score in Arthritic Hip - Marahatta, Suman Babu (Europasian Journal of Medical Sciences, 2020)
Background: Total hip arthroplasty (THA) is a well-established procedure for advanced arthritis of hip joint. It significantly improves the quality of life by relieving pain and improving functional disability. The objective of this study was to evaluate clinical and functional outcome of primary total hip arthroplasty using Harris Hip Score. Method: Prospective study was conducted in Civil Service Hospital. Out of 145 total hip arthroplasties performed from Jan 2014 to Dec 2018, first 100 cases that fulfilled the inclusion criteria were analyzed. Patient demographic including age, sex, site, operative indication and pre-operative Harris Hip Score were documented. Operative time, total intraoperative blood loss and complications were noted. Patients were followed in 3 weeks, 6 weeks, 3 months, 6 months and yearly. In each visit clinical evaluation using Harris Hip Score and radiological evaluation was done and documented. Duration of follow up ranged from minimum of 12 months to maximum 4.5 years. Results: Age varied from 21 to 75 years, 59% were male and 41% female, right side involvement was seen in 55% and left side in 45%. Major indication for surgery was avascular necrosis 46% and primary osteoarthritis in 24%. Average operative time was 65 minutes and average intra operative blood loss was 655 ml. Pre-operative Harris Hip Score ranged from 25 to 59 with mean of 45.5. The mean Harris hip score in last follow up increased to 90.5 with a minimum of 76 and maximum of 97. Our study found that 85% had excellent, 9% had good and 6% had fair results. Complications include 2% dislocation, 1% infection, 1% greater trochanter avulsion and 1% screw irritation. Conclusion: Primary Total hip arthroplasty is a safe and effective procedure. It improves pain and function hence improving activity of daily living and has fewer complications.